Leaflet reconstructive techniques for aortic valve repair - Mazzitelli, Domenico; Stamm, Christof; Rankin, J Scott; Pfeiffer, Steffen; Fischlein, Theodor; Pirk, Jan; Choi, Yeong-Hoon; Detter, Christian; Kroll, Johannes; Beyersdorf, Friedhelm; Shrestha, Malakh; Schreiber, Christian; et al. (The Annals of thoracic surgery, 2014)
BACKGROUND: Refining leaflet reconstruction has become a primary issue in aortic valve repair. This descriptive analysis reviews leaflet pathology, repair techniques, and early results in a prospective regulatory trial of aortic valve repair. METHODS: Sixty-five patients underwent valve repair for predominant moderate to severe aortic insufficiency (AI). The mean age was 63 ± 13 years, and 69% of the patients were male. Ascending aortic/root replacement was required in 62%. As a first step, ring annuloplasty was performed, and then leaflet repair included leaflet plication for prolapse, nodular unfolding, double pericardial patching of commissural defects or holes, complete pericardial leaflet replacement, leaflet extension, and Gore-Tex reinforcement. Leaflet techniques and causes of adverse outcomes were evaluated. RESULTS: The follow-up time was 2-years maximal and 0.9 years mean, with a survival of 97%. Eighty percent of patients required repair of leaflet defects: leaflet prolapse (52/65-80%), ruptured commissures (6/65-9%), leaflet holes (4/65-6%), and nodular retraction (6/65-9%). The average preoperative AI grade of 2.9 ± 0.8 fell to 0.7 ± 0.7 (p < 0.0001). Three patients (4.6%) required interval valve replacement because of (1) suture untying, (2) iatrogenic leaflet tear, or (3) diphtheroid endocarditis. Five other patients experienced grade 2 or grade 3 AI: probable suture untying in 1 patient, ineffective leaflet extensions in 2 patients, and unsuccessful Gore-Tex reinforcements in 2 patients. Two patients with single pericardial leaflet replacements and all those with double pericardial reconstructions did well. CONCLUSIONS: Leaflet defects are common in patients with moderate to severe AI. Leaflet plication, nodular unfolding, and double pericardial patching performed well. Gore-Tex and leaflet extension seemed less satisfactory. Standardization and experience with leaflet reconstruction will be important for optimizing the outcomes of aortic valve repair.
Keywords: anuloplastika srdeční chlopně; aortální insuficience; Humans; lidé středního věku; Cardiac Valve Annuloplasty; Pericardium; Female; Aged; dospělí; výsledek terapie; senioři; lidé; časové faktory; Surgical Flaps; Adult; perikard; Follow-Up Studies; ženské pohlaví; Male; šicí techniky; Echocardiography, Transesophageal; Middle Aged; Retrospective Studies; Treatment Outcome; Aortic Valve Insufficiency; Aged, 80 and over; chirurgické laloky; echokardiografie transezofageální; senioři nad 80 let; retrospektivní studie; Suture Techniques; mužské pohlaví; aortální chlopeň; Time Factors; následné studie; Aortic Valve